On the Number of Spanning Trees of Graphs - Ş. Burcu Bozkurt; Durmuş Bozkurt (The Scientific World Journal, 2014)
We establish some bounds for the number of spanning trees of connected graphs in terms of the number of vertices (n), the number of edges (m), maximum vertex degree (Δ1), minimum vertex degree (δ), first Zagreb index (M1), and Randić index (R-1).